From classrooms to cross-borders: early childhood educator preparation in the Philippines and its influence on migration decisions - Castulo, Nilo Jayoma; Marasigan, Arlyne C.; Macahilig, Heidi B.; Serafico-Reyes, Nikolee Marie A.; Taddese, Esayas Teshome (Frontiers in Sociology, 2025)
IntroductionThe Philippines faces significant challenges in its Early Childhood Education (ECE) sector, including issues of quality, teacher preparation, and the growing trend of educator migration, which threatens the sustainability of the workforce. This study explores the current status of Philippine Early Childhood Education, including its systemic challenges in ECE teacher preparation, and the influence of migration intentions among ECE stakeholders across selected Philippine Teacher Education Institutions (TEIs).MethodsA qualitative case study design was employed, involving 40 key informant interviews and focus group interviews (administrators, cooperating teachers, faculty members, and pre-service teachers) across five state-funded Philippine Teacher Education Institutions (TEIs) designated as Centers of Excellence. Data were analyzed thematically using the push-pull migration theory and professional identity theory.ResultsThe findings showed that ECE stakeholders perceived low programme quality, limited career advancement, financial instability, inadequate institutional support, and societal stigma. Systemic challenges in ECE teacher preparation include real-world misalignment of the curriculum, resource limitations, insufficient training and support, and administrative challenges. Factors that influence migration intention include higher compensation, demand from recruitment agencies, better opportunities abroad, family sacrifices, and educational and professional development.DiscussionThis study showed that migration is both a response to systemic inequalities and an expression of professional autonomy. Furthermore, we investigated effective strategies for retaining ECE teachers in comparable countries within the Global South to gain transferable insights. Although the study’s findings cannot be universally applied to the entire context of the Philippines, they provide valuable insights into the realities of ECE teacher demand and supply, as well as the challenges faced domestically.